1978
DOI: 10.1159/000102399
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Amygdalotomy for Convulsive and Behavioral Disorders

Abstract: 58 patients, whose convulsions and behavioral disorders did not respond to nonsurgical therapy, were treated with stereotactic amygdalotomy between 1963 and 1973. A retrospective study was carried out by a psychiatric research team 1–11 years postoperatively. Using reliable objective methods of assessment they found that 50% operated primarily for seizures, 33% for uncontrolled conduct disorders and 50% with both conditions seemed improved after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…The method of patient selection and assessment, surgical approach, the specific amygdalar nuclei targeted for the procedure, and the size of the lesions created have varied across operators, making direct comparison of outcomes difficult [48]. Generally, the patients treated are described has having less aggressive behavior and a reduction in hyperactivity [48][49][50][51]. Posterior medial hypothalamotomy also has been done alone or in combination with amygdalotomy, for the treatment of aggression [49,52,53].…”
Section: Intractable Aggressionmentioning
confidence: 99%
“…The method of patient selection and assessment, surgical approach, the specific amygdalar nuclei targeted for the procedure, and the size of the lesions created have varied across operators, making direct comparison of outcomes difficult [48]. Generally, the patients treated are described has having less aggressive behavior and a reduction in hyperactivity [48][49][50][51]. Posterior medial hypothalamotomy also has been done alone or in combination with amygdalotomy, for the treatment of aggression [49,52,53].…”
Section: Intractable Aggressionmentioning
confidence: 99%
“…[1][2][3][4][5]7,[12][13][14][15]24,26,[32][33][34]39,40,45,46 It must be emphasized that a comparison of the results of these series is meaningless given the nonhomogenous populations studied, the differences in the surgical technique applied, and the significantly varying outcome criteria. It has been demonstrated that the amygdala in humans consists of 23 distinct subnuclei, which have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of procedure-related complications has varied significantly among published clinical series. [1][2][3][4][5]7,[12][13][14][15]24,27,[32][33][34]39,40,[44][45][46] Hitchcock and Cairns 14 reported no procedure-related complications and no postoperative impairment in the intellectual functioning of their patients. Similarly, Balasubramaniam and Ramamurthi 4 reported no postoperative cases of Klüver-Bucy syndrome, memory deficits, or hypersexuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients became seizure-free and four experienced significant reduction in seizure severity and frequency. Heimburger et al 9 performed amygdalotomy in 58 patients for control of seizures and/or behaviour disorders. Seizures were described as psychomotor, petit mal and grand mal.…”
Section: Stereotactic Amygdalotomy Hippocampotomymentioning
confidence: 99%